Innocents Abroad? The Consumption of Antiquities from the Holy Land - Kersel, Morag M. (Journal of ancient Judaism, 2023)
Why do people want to own a piece of the past? What tempts consumers? What effect does consumption have on archaeological landscapes? Generally, Holy Land consumers can be broken down into two categories: those on the low-end interested in small mementoes of a trip, and those on the high-end, wealthier individuals willing to make financial investments for the highest quality pieces. Whether buyers are wily speculators, investing to increase their capital (cultural, economic, social, sensu Bourdieu), or innocent pilgrims on a once in a lifetime trip to the Holy Land, the result is the same: looting and theft from archaeological sites in order to meet consumer demand for archaeological artifacts. With data gathered from archaeological ethnographies, this article assesses the purchasers of artifacts, the unintended consequences of their acquisitions, and considers the ways we might create a set of better-informed consumers in the licensed antiquities market in Israel.